Effect of zeolite and pumice powders on the environmental and physical characteristics of green concrete filters. (20th April 2020) - Azad, Armin; Saeedian, Amir; Mousavi, Sayed-Farhad; Karami, Hojat; Farzin, Saeed; Singh, Vijay P.
Highlights: Using zeolite enhances the filter ability in reducing pollution parameters of wastewater types. Using pumice enhances the filter ability in reducing pollution parameters of wastewater types. Using zeolite and pumice materials do not deteriorate the physical properties of porous concrete. Abstract: Green porous concrete (GPC) is a porous concrete (PC) with minimum amount of cement. This study investigated the effects of zeolite and pumice, as cementitious materials, on the physical properties of PC and the enhancement of its ability to reduce urban and industrial runoff pollution. GPC specimens were prepared by replacing cement with zeolite and pumice in different portions (10–40%). Results indicated that pumice had a better physical performance but zeolite had a greater ability to enhance GPC performance in improving wastewater quality. Furthermore, zeolite and pumice reduced the apparent density of concrete up to 181 and 92 kg/m 3, respectively. Also, GPC performed well in eliminating TSS and turbidity. The use of 40% zeolite improved the ability of PC to reduce chemical oxygen demand (COD), Zinc (Zn), Copper (Cu), Cadmium (Cd) and Lead (Pb) by 38.6, 99, 99, 99 and 99%, respectively. The reductions in these water quality parameters due to the addition of 40% pumice were 25.4, 98, 96, 99 and 99%, respectively.